Helminthosis of cattle of private economies of Poltava region - Клименко, О. С.; Клименко, І. І.; Мазуріка, В. В.; Юрченко, Ю. В. (Scientific Progress & Innovations, 2012)
The results of coprological researches of cattle of private economies of the Poltava region are in-process resulted. Researches are set parasitizing of Fasciola, Dicrocoelium, Paramphistomum and intestynal Strongylata as mono- and poliinvasion. The extensiveness of helminthosis is 6,25–35,7 %, and intensity – 0,3–4,3 pc. / 1 g. The high degree of invasion of animals confirms actuality of the noted problem, that is why the prospect of subsequent researches is obligatory development and introduction in the private households of measures of fight against helminthosises.